Zandtfuro and Schernfeldfuro, new genera of Halecomorphi (Actinopterygii) from the Upper Jurassic Solnhofen Archipelago. Issue 2 (4th March 2019) - Ebert, Martin
ABSTRACT: In the Late Jurassic Plattenkalk deposits of the Solnhofen Archipelago and of Nusplingen (both southern Germany), there are a considerable number of as yet undescribed genera and species of ganoin-scaled Halecomorphi. Some species were preliminarily assigned to the genus ' Furo '; however, as noted by previous authors, the taxon ' Furo ' is not a monophyletic genus. A description of two new genera and species, Zandtfuro tischlingeri and Schernfeldfuro uweelleri is presented here, with further descriptions of new species to follow separately. These new taxa are characterized by a specific combination of features, including: body shape; number of suborbital bones, infraorbitals, extrascapulars, dorsal and caudal fin rays, and vertical scale rows; number and shape of maxillary teeth; presence or absence of sclerotic ring ossification; shape of the ventral postinfraorbital; insertion of dorsal, pelvic, and anal fins; position of lateral line in caudal fin area; and shape and distribution of scales. The more basal Halecomorphi with massive ganoin scales (Parasemionotiformes, Panxianichthyformes, and Ophiopsiformes) remain poorly known, compared with the more advanced halecomorph group of the Amiiformes (especially the Amiidae). Closer investigation of their taxonomic relationship is therefore important for understanding broader patterns of halecomorph evolution.